Effects of Curcuma Longa Ethanol Extract on Isolated Guinea Pigthile Smooth Muscle in Acetylcholine Induction - Zheng Yuebin; Florenly; Liena; Fioni (Britain International of Exact Sciences (BIoEx) Journal, 2022)
Epidemiological studies show that nearly 20% of the world's population suffers from diseases related to allergies and asthma. The main compound of turmeric is curcumin has several pharmacological properties, antioxidant properties, anti-inflammatory, asthma treatment. The study aimed to determine the effects of ethanol extract Curcuma longa on the smooth muscle of the isolated guinea pigtic trachea in acetylcholine induction. This research method was experimental to observe the relationship of Curcuma longa ethanol extract (EECL) to the relaxing effects of isolated smooth muscle trachea marmot (tracheal ring chain) inserted into a bath organ filled with Kreb's physiological fluid by maintaining a temperature of 35-370C and associated with a Matlab recorder. Samples used by male guinea pigs and ethanol extract Curcuma longa (EECL). The results of the study that ethanol extract Curcuma longa has a relaxing effect on the smooth muscles of the trachea isolated from the experimental rats contracted with acetylcholine. Ethanol extract Curcuma longa has the ability not dising from theophylline 2 x 10-4 M in reducing smooth muscle contraction of insulated Cavia porcelain trachea induced by acetylcholine, acetylcholine strength without incubation contraction compared to acetylcholine with EECL incubation showed statistically different results (p <0.05). The mechanism of Curcuma longa relaxation effect on isolated guinea pig smooth muscle is mediated through inhibition of the enzyme PDE.